Transgression and tenderness. Olga Tokarczuk in Comparative Perspective - Sobczak, Izabela (Porównania, 2023)
The article is a review of the recently published by Routledge anthology Olga Tokarczuk. Comparative Perspectives, edited by Lidia Wisniewska and Jakub Lipski. As the first alngo-language monograph on Tokarczuk, supported by a concrete methodological proposal, it finds a significant place in the international discourse of the author. In the Polish literary discourse, which has been divided, it also opens new interpretative paths. The authors of the anthology, passing the boundaries of traditional comparative literature, highlight the epistemological aspect of Tokarczuk’s work, the way of understanding the “bizarness”, as well as the sources of her aesthetics. It turns out that the social dimension of Tokarczuk's prose, also gains a personal character, and the tender narrator, moving along the comparative path, has a chance to break out of abstraction towards subjectivity.